2009
DOI: 10.1136/thx.2008.105718
|View full text |Cite
|
Sign up to set email alerts
|

Rosai-Dorfman disease of the lung

Abstract: Rosai-Dorfman disease is a rare disorder which seems to involve not only the lymph nodes but most other organs of the body. The case history is presented of a woman who was thought to have atypical carcinoma of the lung but in whom a diagnosis of Rosai-Dorfman disease was eventually made following a range of investigations including CT scans, positron emission tomography (PET) and histological analysis of open lung biopsy specimens. She remains well with no further progression of the disease without treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
1
10
1
Order By: Relevance
“…Those are founded with accounting for 40% of RDD. On the other hand, intrathoracic manifestations of RDD are rare and represent only 2% of the cases with RDD (Foucar et al 1990), and only 9 cases of RDD with localized intrathoracic lesions have been reported (Table 1) (Ohori et al 2003;Shi et al 2009;Ali and Mackay 2009;Hida et al 2009;Zhou et al 2010;Roberts and Attanoos 2010;Cartin-Ceba et al 2010;Kaseda et al 2011). The discriminative pathological findings of the present patient were diffuse bronchial proliferation of histiocytes with round or oval shaped nuclei and clear and weakly acidophilic cytoplasm (McClain et al 2004).…”
Section: Clinical Reportmentioning
confidence: 85%
See 1 more Smart Citation
“…Those are founded with accounting for 40% of RDD. On the other hand, intrathoracic manifestations of RDD are rare and represent only 2% of the cases with RDD (Foucar et al 1990), and only 9 cases of RDD with localized intrathoracic lesions have been reported (Table 1) (Ohori et al 2003;Shi et al 2009;Ali and Mackay 2009;Hida et al 2009;Zhou et al 2010;Roberts and Attanoos 2010;Cartin-Ceba et al 2010;Kaseda et al 2011). The discriminative pathological findings of the present patient were diffuse bronchial proliferation of histiocytes with round or oval shaped nuclei and clear and weakly acidophilic cytoplasm (McClain et al 2004).…”
Section: Clinical Reportmentioning
confidence: 85%
“…It was reported that around 40% of RDD patients have lymph node disorders and extranodal involvement, but intrathoracic manifestations of RDD was reported in only 2% of patients with RDD (Foucar et al 1990). Furthermore, there have been only 9 cases of RDD with localized intrathoracic lesions (Ohori et al 2003;Shi et al 2009;Ali and Mackay 2009;Hida et al 2009;Zhou et al 2010;Roberts and Attanoos 2010;Cartin-Ceba et al 2010;Kaseda et al 2011). No standard treatment for RDD has yet been established, but a good prognosis has been reported (Foucar et al 1990), and another report (Gotou et al 2008) noted that 20% of the cases showed spontaneous remission.…”
mentioning
confidence: 99%
“…Some hypothesise that Rosai-Dorfman disease is a reactive pattern in response to an (viral) infection, but the true cause remains unknown [2]. Extranodal disease involvement (pulmonary, kidney and skin) has been described previously [3].…”
Section: To the Editorsmentioning
confidence: 99%
“…Airway involvement by relapsing polychondritis, which results in tracheobronchomalacia and airway stenosis, is associated with a poor prognosis.Several reports have suggested that endobronchial intervention can be beneficial in these subjects [2,3]. Herein, we describe a case of bronchial rupture related to endobronchial intervention in a patient with relapsing polychondritis.…”
mentioning
confidence: 99%
See 1 more Smart Citation